Studio and cube on the relationship between where art is made and where art is displayed - O'Doherty, Brian (Buell Center/FORuM Project publication, 2007)
Features photographs of the studios of such artists as Lucas Samaras, Vito Acconci, Jackson Pollock, Lowell Nesbitt, Louise Nevelson, Claes Oldenburg, Pablo Picasso, Max Ernst, Robert Rauschenberg, Francis Bacon, Mark Rothko, Henri Matisse, Piet Mondrian, and Constantin Brancusi.